Development of the MICADO Flat-field and Wavelength Calibration Unit: From Design to Prototyping. (17th November 2020) - Rodeghiero, Gabriele; Häberle, Maximilian; Sauter, Jonas; Sawczuck, Miriam; Pott, Jörg-Uwe; Münch, Norbert; Ramos, José Ricardo; Naranjo, Vianak; Kausch, Wolfgang; Sabha, Nadeen B.; Biancalani, Enrico; Barboza, Santiago; et al.
Abstract: We describe the evolution and the analysis of the design that led to the development of the Flat-field and wavelength Calibration Unit (FCU) for the Multi-AO Imaging CAmera for Deep Observations (MICADO) instrument. MICADO will be one of the first light instruments of the Extremely Large Telescope. The FCU challenge in terms of calibration is related to the large size of the MICADO entrance and final focal plane, ∼200 mm × 200 mm. Such a focal plane scale and its segmentation in 3 × 3 detectors, require significant design modifications with respect to the calibration units of the current and past generation of instruments. The design analysis and ray tracing calculations are complemented with the test and verification of lab prototypes to assess the reliability of the FCU architecture in terms of flat-field illumination uniformity and signal to noise, spectral calibration line coverage and radial velocity stability of the wavelength solution provided to the instrument.